STRATEGIC DEVELOPMENT OF COMPANIES IN THE MARKET OF INFORMATION AND COMMUNICATION TECHNOLOGIES: CONTENT, APPROACHES AND KEY DIRECTIONS - LARINA, Yaroslava; DICHENKO, Anna; NIKOLENKO, Inessa (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the approaches of scientists to defining the essence of strategic development, considers modern approaches to management based on marketing, determines the sequence of stages of strategic management of enterprise development, which is a relevant issue in the context of achieving strategic goals of the enterprise. The purpose of the article is to substantiate the theoretical and methodological foundations and directions of strategic development of enterprises in the ICT market. To realize the set goal, the following tasks were set: clarify the categorical and conceptual apparatus in the field of strategic development; determine the place and features of strategic development in the enterprise management system; determine the key trends in the development of enterprises in the ICT market, which determine the need for changes in the management system of enterprises in the direction of strengthening strategic analysis and the application of modern marketing concepts; determine directions of strategic development modeling in the management system of enterprises in the ICT market. It was proved that strategic development is not a self-organized process, its success depends on the adoption of specific managerial strategic decisions. Strategic development of an enterprise on the ICT market in modern conditions is impossible without building an effective strategic management system based on marketing principles and modern marketing concepts. In order to ensure managed successful development on the market, the enterprise must define long-term goals and objectives, justify the concept of alternative and adaptive activity and development, make management decisions regarding the identification of areas and directions of resource provision by the enterprise for the long term, taking into account the opportunities and threats that may arise by selected areas and areas of resource use, i.e. by selected areas of activity (SBU, areas of business, innovative products or services of the enterprise for specific markets). The ICT industry is rapidly developing, guided by the imperative of digitization and innovative integration of AI technologies. Key trends in the ICT market include: digitalization processes, virtual sales, active involvement of artificial intelligence, metauniverse, changing forms and methods of competition, joint consumption of corporate technologies, creation and use of joint innovation ecosystems. As companies navigate virtual sales strategies, the rise of avatars underscores the importance of the metaverse. In addition, competition in the field of ICT is intensifying, which requires providers to constantly improve their technological capabilities. Essentially, these new trends in ICT highlight the industry's drive to adapt, innovate and meet the dynamic needs of global and local customers. It is appropriate to take into account these trends in the process of planning and implementing marketing plans and programs of ICT enterprises and telecommunications business.
Keywords: strategic management of enterprise; strategic development; strategic management process; ICT market; digitalization; global competition